Survival analysis of dogs with advanced primary lung carcinoma treated by metronomic cyclophosphamide, piroxicam and thalidomide. (6th March 2018) - Polton, G.; Finotello, R.; Sabattini, S.; Rossi, F.; Laganga, P.; Vasconi, M. E.; Barbanera, A.; Stiborova, K.; Rohrer Bley, C.; Marconato, L.
Abstract : Unresectable or metastatic (advanced) primary pulmonary carcinoma (PPC) represents a therapeutic challenge where surgery may be contraindicated and the therapeutic role of maximum‐tolerated dose (MTD) chemotherapy remains uncertain. This study was undertaken to explore the impact of metronomic chemotherapy (MC) in dogs with advanced PPC. Previously untreated dogs with advanced (T3 or N1 or M1) PPC, with complete staging work‐up and follow‐up data, receiving MC (comprising low‐dose cyclophosphamide, piroxicam and thalidomide), surgery, MTD chemotherapy or no oncologic treatment were eligible for inclusion. For all patients, time to progression (TTP) and survival time (ST) were evaluated. Quality‐of‐life (QoL) was only evaluated in patients receiving MC. To assess QoL, owners of dogs receiving MC were asked to complete a questionnaire before and during treatment. Ninety‐one dogs were included: 25 received MC, 36 were treated with surgery, 11 with MTD chemotherapy and 19 received no treatment. QoL was improved in dogs receiving MC. Median TTP was significantly longer in patients receiving MC (172 days) than patients undergoing surgery (87 days), receiving MTD chemotherapy (22 days), or no oncologic treatment (20 days). Median ST was similarly longer in patients receiving MC (139 days) than those undergoing surgery (92 days), MTD chemotherapy (61 days) and no oncologic treatment (60 days). In dogs with advanced PPC, MC achieved a measurable clinical benefit without significant risk or toxicity. This makes MC a potential alternative to other recognized management approaches.